OBLIGATORY BEQUEST IN THE CONTEXT OF POLYGAMOUS WIVES: PRESERVING EQUALITY AND JUST WITHIN THE FRAMEWORK OF MAQASHID SHARIA - Rizki Lubis, Rusdi; Arfaizar, Januariansyah; Segara Gustanto, Edo (Universitas Islam Indonesia, 2024)
This paper discusses the role of obligatory bequests in the context of the relationship between a secret wife in the context of polygamous marriage outside the judicial procedure, with an emphasis on maintaining equality and justice, within the framework of understanding Maqasid Sharia. A secret wife is a complex issue in the implementation of Islamic family law in Indonesia, and this research outlines the concept of obligatory bequests and their role in maintaining a balance of inheritance between a legitimate wife and a secret wife. By using the principles of equality and justice in Islam as a guide, this research illustrates how the path of obligatory bequests can lead to a more equitable distribution of inheritance among heirs. Additionally, this paper integrates the concept of Maqasid Sharia as a philosophical foundation for understanding the importance of maintaining equality and justice in Islamic inheritance law. The results of this writing are expected to provide deeper insights into how the concept of obligatory bequests can contribute meaningfully to achieving the highest goals of Maqashid Sharia, including ensuring equality and justice in the distribution of inheritance for secret wives in polygamous marriages outside the judicial procedure.